Electrokinetic remediation of PPCPs in soil: influence of soil biota and environmental factors - Dionísio, Joana Magalhães (2019)
The use of treated wastewater for agricultural irrigation, is a common practice in several countries as it has several benefits, such as decreasing pressure on freshwater sources and reduced nutrient loads to receiving waters. However, wastewater treatment plants (WWTP) are not always able to remove all the contaminants present, thus representing a significant risk for environmental contamination. Soil contamination by wastewater may potentially promote contaminants uptake and accumulation by plants and derived products which consequently can affect human health. Pathogens and heavy metals are traditionally the main concern, however contaminants of emerging concern (CECs), and particularly pharmaceutical and personal care products (PPCPs), are gaining scientific and public attention. In the present dissertation, the electrokinetic (EK) process was applied as a remediation technology to an agricultural soil contaminated with a mixture of PPCPs. To better understand the remediation mechanisms involved, different assays were developed to discriminate biotic, abiotic and EK contributions, alone and coupled, to the degradation of the PPCPs. As environmental factors may affect the remediation processes, trials with and without irrigation and at different temperatures were also conducted (18 and 24 ºC). As contaminants, 10 commonly environmentally occurring PPCPs were selected for the study: 17β-estradiol (E2), sulfamethoxazole (SMX), bisphenol A (BPA), ibuprofen (IBU), 17α-ethinylestradiol (EE2), oxybenzone (OXY), triclosan (TCS), diclofenac (DCF), caffeine (CAF) and carbamazepine (CBZ). These compounds represent the major PPCPs classes and attain diverse physicochemical properties. All experiments were carried out in a lab scale microcosm using a 12h ON/OFF current mode at 20 mA for 4 days (in duplicates). The best remediation results were attained when EK process was applied in biotic conditions at 24ºC and combined with a daily irrigation (EK-Biotic-24-W); these conditions allowed to remove approximately 37% of the total mass on PPCPs in the soil. By eliminating the microbiological contribution to the degradation processes (sterilized soil; abiotic setting) in the same EK conditions (EK-Abiotic-24-W) a decrease in the removal by 7% was observed. The abiotic removal mechanisms only contributed to a total mass decay of 6%, whereas the biotic mechanism removed 20% (at 24ºC). The PPCPs more recalcitrant to degradation were CBZ, OXY and TCS. Oppositely E2, SMX e BPA displayed to be more biodegradable. Such results are compatible with previous tests, which suggest that usage of EK in combination with bioremediation vastly improves the efficiency over that of EK remediation alone in removing pollutants from soil. The EK process showed to be an effective option for the remediation of PPCPs in clay soils, which may enhance the degradation of contaminants by two main remediation mechanisms: (i) electrochemical induced degradation and (ii) bioremediation.